Understanding childhood hearing loss : whole family approaches to living and thriving - Fligor, Brian J., 1974- (Lanham : Rowman & Littlefield, 2015)
Childhood hearing loss is more common than most people assume, and yet this invisible condition can rob a child of the ability to develop close emotional relationships with family and friends. This book demystifies this condition and offers approaches to caring for the child and the whole family. It is written from the perspective of a pediatric audiologist who has diagnosed hearing loss in hundreds of newborns and young children, and who has shaped clinical best-practices during his career. Hearing loss is not an all or nothing condition, but a range from very subtle, slight challenges, to very little ability to hear. The impact that hearing loss can have on a child's language, intellectual, social, and emotional development is enormous. But when the team of healthcare providers, developmental specialists, and parents are all working together, the hearing loss can become just another trait of this child, rather than the single condition that defines the child and the family's experience raising that child. This book offers an explanation of what is hearing loss for parents, describes who is on the team working with the child (and team members roles), and practical guidance for navigating what can be an uncertain path for families.
Welcome to Holland ... A clinician's perspective -- What is hearing loss? How did this happen? -- How hearing is tested in infants and young children -- The impact of childhood hearing loss -- How is hearing loss treated? -- Beyond devices: How do you know interventions are working? -- Members of the management team -- Experiences and practical advice -- Understanding childhood hearing loss.
Includes bibliographical references (pages 171-187) and index.
Keywords: Hard of hearing children -- Rehabilitation; Hard of hearing infants -- Rehabilitation; Hearing disorders in children; Hearing disorders in infants; Deaf children